2013
DOI: 10.1111/are.12353
|View full text |Cite
|
Sign up to set email alerts
|

Why is cannibalism less frequent when larvae of sutchi catfishPangasianodon hypophthalmusare reared under dim light?

Abstract: Survival rates of the larvae of sutchi catfish Pangasianodon hypophthalmus are reported to be three times higher under dim conditions (0.1 lx) than those under 100 lx. In this study, larval behaviour of sutchi catfish was examined under various light intensities (<0.01, 0.1, 1, 10 and 100 lx) using a CCD camera to understand why survival rates vary under different light intensities. Five-day-old larvae showed significantly higher swimming activity under <0.01, 0.1 and 1 lx than those under 10 and 100 lx. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Smaller swimming activity reduces the likelihood of encounters between animals and, therefore, social interactions among group members (Souza et al, ). Thus, in low light conditions, there is a reduction in aggressive behaviour and increased survival as observed in Pangasianodon hypophthalmus (Mukai et al, ) and Sander lucioperca larvae (Tielmann, Schulz, & Meyer, ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Smaller swimming activity reduces the likelihood of encounters between animals and, therefore, social interactions among group members (Souza et al, ). Thus, in low light conditions, there is a reduction in aggressive behaviour and increased survival as observed in Pangasianodon hypophthalmus (Mukai et al, ) and Sander lucioperca larvae (Tielmann, Schulz, & Meyer, ).…”
Section: Discussionmentioning
confidence: 95%
“…The luminosity, for example, is an essential environmental condition for the survival of fish (Rick & Bakker, ). Some studies suggest that the manipulation of light intensity can regulate biological rhythms and modulate various physiological functions in different species of fish, and it may reflect on survival (Mukai, Nai, & Lim, ; Navarro, Navarro, Murgas, & Felizardo, ), growth (Biswas, Morita, Yoshizaki, Maita, & Takeuchi, ; Falcón, Migaud, Muñoz‐Cueto, & Carrillo, ; Imsland et al, ; Rad, Bozaoglu, Gözükara, Karahan, & Kurt, ), food intake (Kitagawa et al, ; Puvanendran & Brown, ), metabolic rate (Porter, Duncan, Handeland, Stefansson, & Bromage, ), locomotor activity (Navarro et al, ; Trippel & Neil, ), body pigmentation, sexual maturation, reproduction (Fujii, Sugimoto, & Oshima, ; Song et al, ), melatonin (Ekström & Meissl, ; Falcón et al, ) and aggressive behaviour (Carvalho, Ha, & Gonçalves‐de‐Freitas, ; Carvalho, Mendonça, Costa‐Ferreira, & Gonçalves‐de‐Freitas, ; Lopes et al, ; Sarmento, Almeida, Marcon, & Carvalho, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Mukai 216 found that P. hypophthalmus larvae showed higher survival and growth rates when reared under 0.1 lx (1.40 × 10 −3 μmol m −2 s −1 ) of white fluorescent light compared with those reared under other light intensities (1, 10, and 100 lx). Moreover, Mukai et al 217 demonstrated that P. hypophthalmus larvae showed more aggressive behaviour at higher light intensities (10 and 100 lx) than those under low light intensity (0 and 0.1 lx); these results corroborate those reported for C. gariepinus 213 . Furthermore, when C. gariepinus larvae were reared under normal photoperiod (600–1000 lx during light hours) or continuous dark (<0.01 lx) conditions from hatching up to 20 dph, no differences in larval size were found, even though larvae reared under dark conditions had higher survival rates than those under normal photoperiod 89 .…”
Section: Cannibalism In Early Life Stagesmentioning
confidence: 99%
“…In previous studies, under white fluorescent light, sutchi catfish larvae were reported to exhibit significantly higher survival rate and lower cannibalism under dim light conditions than bright light conditions (Mukai, Tan, & Lim, ; Mukai, ). Moreover, under red light with a light intensity of 1.40 × 10 −3 µmol m −2 s −1 , sutchi catfish larvae showed a tendency to have higher survival and growth rates (Tan, Yusoff, Ismail, Sallehudin, & Mukai, ), while sutchi catfish juveniles showed a tendency to have higher growth rates and production index (Tan, ).…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, taking into account the reported species‐specific visual spectral sensitivity among fish and the dearth of studies on the sensitivity of sutchi catfish towards light conditions (Mukai et al, ; Mukai, ; Tan, ; Tan et al, ; Yusoff, Sallehudin, Tan, Mohammad‐Noor, & Mukai, ), this study aimed to understand the visual spectral sensitivity of juvenile sutchi catfish through the peak differences in spectral absorbance of wholemounts of retinae by spectrophotometric analyses.…”
Section: Introductionmentioning
confidence: 99%